The Quality Management Assistance Of Financial Governance On Ud “Dua Putra” Rice Mill Business In Kutorenon Sukodono - Jariah, Ainun (Empowerment Society, 2020)
The activity aims to provide quality management assistance of financial governance on UD “DUA PUTRA” rice mill business in Kutorenon Sukodono, so that the company is able to improve the human resources ability in managing its business management; strengthen the human resources ability in the preparation of bookkeeping regularly and correctly; improve the ability to separate between business and household finances; find easy capital access. The method used in this community service activity has several stages, including initial surveys, interviews in order to find offered problems and solutions, business management assistance, financial management and UKM operational funding assistance. The weakness of partner mainly lies in the limited human resources ability in manage their business, the unavalaibility of human resources who understand business bookkeeping regularly, unseparated business and household finances and limited capital access. Targets to be achieved, include: increase partner skills in running its business sustainably; strengthening the ability of partners in the preparation of bookkeeping regularly and correctly; increasing the ability of partners in separating business and household finances and obtaining easy capital access.